Customer Satisfaction Towards Service Quality: A Study of Malindo Air - Nabilah Maisarah; Daisy Mui Hung Kee; Nurul Syakirah; Mohd Azri Hanif; Arti Bella; Rudresh Pandey; Rashed Fahad Almuhaini; Majdi Anwar Quttainah (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
In any business, customers are the main sources that contribute to revenue and keep the business going on, year by year passes. People may think that the aviation industry is one of the highest costs in transportation, but if compared to the services and benefits offered, it should be considered as worth money paid. The discussion throughout the paper focuses on passengers’ satisfaction with the service quality provided by Malindo Air. To collect the data on customer satisfaction, a survey on Malindo Air was conducted. The results of the findings demonstrated that service quality is critical to maintaining the passengers' satisfaction.